Low-Noise Analog Channel for the Readout of the Si(Li) Detector of the GAPS Experiment - Manghisoni M.; Re V.; Riceputi E.; Sonzogni M.; Ratti L.; Fabris L. (IEEE Transactions on Nuclear Science, 2021)
This work is focused on the design and the experimental characterization of an analog channel developed for the readout of lithium-drifted silicon detectors of the General AntiParticle Spectrometer (GAPS) experiment aimed at the search for dark matter. The instrument is designed for the identification of antideuteron particles from cosmic rays during an Antarctic balloon mission scheduled for late 2022. A low-noise analog front-end, featuring a dynamic signal compression to comply with the wide input range, has been designed in commercial 180-nm CMOS technology. The channel was fabricated in 2018 and is the first building block toward the development of a multichannel readout ASIC. The article will provide a description of the design criteria, the architecture of the channel, and a summary of the results of the experimental characterization.